The data acquisition system of the Latin American Giant Observatory (LAGO) - Sofo Haro, Miguel Francisco (2016)
LAGO is an extended cosmic ray observatory composed of water-Cherenkov detectors (WCD) placed throughout Latin America. It is dedicated to the study of various issues related to astrophysics, space weather and atmospheric physics at the regional scale. In this paper we present the design and implementation of the front-end electronics and the data acquisition system for readout of the WCDs of LAGO. The system consists of preamplifiers and a digital board sending data to a computer via an USB interface. The analog signals are acquired from three independent channels at a maximum rate of 1:2 105 pulses per second and a samplingrate of 40 MHz. To avoid false triggers due to baseline fluctuations, we present in this work a baseline correction algorithm that makes it possible to use WCDs to study variations of the environmental radiation. A data logging software has been designed to format the received data. It also enables an easy access to the data for an o-line analysis, together with the operational conditions and environmental information. The system is currently used at dierent sites of LAGO.